Sensing Properties of ZnO-SWCNT Hybrid Nanostructure Coated on Flexible Substrate for CO2 Gas Detection - Aisyah Nur Estri; Riyani Tri Yulianti; Qonitatul Hidayah; Surip Kartolo; Rike Yudianti (BRIN Publishing (Penerbit BRIN), 2022)
We report sensing properties of functionalized single walled carbon nanotubes (f-SWCNTs) deposited on the flexible substrate of silicon (Si) and polyethylene tereptaphalate (PET). Deposition of f-SWCNT on Si rubber and PET surface was conducted by applying different manner of spray coating and dip coating techniques, respectively. Surface modification of f-SWCNT by ZnO nanostructure layer were applied by hydrothermal process.The research study were conducted to know the effect of substrate material and ZnO structure on the f-SWCNT surface which embedded in those flexible polymer substrates. The results reveal that f-SWCNT on Si substrate (f-SWCNT/Si) do not have a good response in gas sensing performance. In meanwhile f-SWCNT on PET substrates (f-SWCNT/PET) is more sensitive about 1.6% with 3s in response. ZnO structure layer modifying the surface structure of f-SWCNT enhance the sensitivity and responsiveness of the sensor with sensitivity of 4.1 % in 2s response after CO2 injection. Effect of bending treatment of the sensor and its stability were further investigated. Morphological surface of f-SWCNT network and crystal structure of ZnO and f-SWCNT were also observed by scanning electron microscope (SEM) and X-ray diffraction, respectively